New mechanisms in the socio-labour relationships regulation system - R. V. Kalyakulin (Путеводитель предпринимателя, 2020)
In the article, the author researches the topical issues of the socio-labour regulation system at the aviation industry facilities, analyses goals and objectives of trade unions, offers new ways and mechanisms to involve the labour forces into the corporate operations. One of the main guidelines are competitiveness and social charter.